The Influence of Leadership, Motivation, and Working Environment on Employee Performance in Agriculture Department of Boalemo District, Gorontalo Province - Maman Musa; Susilawati Abdullah (Journal of Economic, Business, and Administration (JEBA), 2020)
The research had purposed to analyze the influence of Leadership, Motivation and Work Environment toward Employees Performance and to determine the variable that had dominant influence on imployees Performance on Department of Agriculture in Boalemo Regency, Gorontalo Province. The research had been done through survey opproach, the sample of research were the employees on Department of Agriculture in Boalemo Regency, Gorontalo Province and the amount about 50 people. The data collected by questioner’s deployment and documentation. Analyzing tool used are validity test, reliability test, and test of classic assumption, multiple linier regression, t test and coefficient determination (R), then the data was processed use the SPSS. Result of research shows that partially work environment had negative and insignificant influence on employee’s performance, while leadership and motivation positively and significant had influence toward imployees performence on Department of Agriculture in Boalemo Regency, Gorontalo Province.